1,3,4, Oxadiazole Compound A3 Provides Robust Protection Against PTZ-Induced Neuroinflammation and Oxidative Stress by Regulating Nrf2-Pathway - Alvi AM; Shah FA; Muhammad AJ; Feng J; Li S (Dove Medical Press, 2021)
Arooj Mohsin Alvi,1,2 Fawad Ali Shah,2 Asmaa Jan Muhammad,2 Jinxing Feng,1 Shupeng Li3 1Department of Neonatology, Shenzhen Children's Hospital Shenzhen, Shenzhen, People's Republic of China; 2Department of Pharmacology, Riphah Institute of Pharmaceutical Sciences, Riphah International University, Islamabad, Pakistan; 3State Key Laboratory of Oncogenomics, School of Chemical Biology and Biotechnology, Shenzhen Graduate School, Peking University, Shenzhen, People's Republic of ChinaCorrespondence: Fawad Ali Shah; Jinxing Feng Email fawad.shah@riphah.edu.pk; szfjx2013@hotmail.comBackground: Epilepsy is a common neurological disorder that is characterized by recurrent episodes of seizures. Various studies have demonstrated a direct association between oxidative stress and inflammation in several neurological disorders including epilepsy. This study aimed to investigate the neuroprotective effects of a synthetic 1,3,4, oxadiazole compound A3 against pentylenetetrazole (PTZ)-induced kindling and seizure model.Methodology: PTZ was administered in a sub-convulsive dose of 40 mg/kg for 15 days, at 48-hour intervals to male Swiss-Albino mice until animals were fully kindled. Two different doses of A3 (10 mg/kg and 30 mg/kg) were administered to find out the effective dose of A3 and to further demonstrate the relative role of nuclear factor E2-related factor (Nrf2) in the PTZ-induced kindled model.Results: Our results demonstrated a compromised antioxidant capacity associated with a low level of catalase (CAT), superoxide dismutase (SOD), glutathione (GST), and glutathione S-transferase (GSH) in the kindled group. However, the PTZ-induced group demonstrated an elevated level of lipid peroxidation (LPO) level parallel to pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), mediators as cyclooxygenase (COX-2), and nuclear factor kappa B (NFκB). Furthermore, the A3 treatment reversed these changes and overexpressed the antioxidant Nrf2 gene and its downstream HO-1. To further investigate the involvement of Nrf2, we employed an Nrf2-inhibitor, ie, all-trans retinoic acid (ATRA), that further aggravated the PTZ toxicity. Moreover, vascular endothelial growth factor (VEGF) expression was evaluated to assess the extent of BBB disruption.Conclusion: The findings of this study suggest that A3 could mediate neuroprotection possibly by activating Nrf2 dependent downregulation of inflammatory cascades.Keywords: epilepsy, PTZ, oxidative stress, Nrf2, HO-1, neuroinflammation